rogreenhoxa8

Answered 2021-08-09
Author has **26324** answers

Vasquez

Answered 2021-12-28
Author has **10750** answers

Step 1

The given expression can be written as:

\(\sqrt[3]{x^{12}}=(x^{12})^{\frac 13} \ \ \ \ (\text{ Since } \sqrt[n]{a}=a^{\frac 1n})\)

\(\sqrt[3]{x^{12}}=(x^{12 \times \frac 13}) \ \ \ (\text{ Since } (a^m)^n=a^{mn})\)

\(\sqrt[3]{x^{12}}=(x^{\frac{12}{3}})\)

\(\sqrt[3]{x^{12}}=x^4\)

Therefore, the given radical expression to its rational exponent form is given by \(\sqrt[3]{x^{12}}=(x^{12})^{\frac 13}\) and the simplifiend form is given by \(\sqrt[3]{x^{12}}=x^4\)

asked 2021-08-12

asked 2021-08-10

asked 2021-08-10

asked 2021-08-15

To determine: The radical form of \(\sqrt[3]{64}\) in the rational exponent form.

asked 2021-08-06

asked 2021-08-07

asked 2021-08-10

To convert the given radical expression to its rational exponent form and then simplify